Effect Of Hydrodynamic Coefficient On Classics Spars Respons - Aishah Radhiah Bt Adanan, Aishah Radhiah (Universiti Teknologi Petronas, 2009)
As a floating strucutre ,the motion of spar platform which connected to the sea bottom anchoring is taken into account. The motions are affected by the nevironmental load such as wind,current and wave. The different type of the dynamic response such as heave,surge,pitch,roll and yaw of the classsic spar platform are being analyzed